2020
DOI: 10.21153/jtlge2020vol11no1art937
|View full text |Cite
|
Sign up to set email alerts
|

Graduate Work-Readiness in Mauritius: A multi-stakeholder approach

Abstract: Characterised by strong human capital dependency, Small Island Development States (SIDS) such as Mauritius depend largely on work-ready graduates to boost their economy. Yet, Graduate Work Readiness (GWR) and graduate unemployment feature prominently on the Mauritian government agenda. This paper investigates the previously unexplored issue of GWR in Mauritius through four key stakeholder lenses – those of the government, employers, universities, and undergraduates – before suggesting collaborative strategies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…The results of this study suggest a set of conclusions which agree with those that are currently being made in the debates about higher education and the employability of graduates. In fact, the results are similar to those of other analogous studies applied in other contexts and territories (Hardin-Ramanan et al, 2020;Mocanu et al, 2014).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results of this study suggest a set of conclusions which agree with those that are currently being made in the debates about higher education and the employability of graduates. In fact, the results are similar to those of other analogous studies applied in other contexts and territories (Hardin-Ramanan et al, 2020;Mocanu et al, 2014).…”
Section: Discussionsupporting
confidence: 90%
“…On the one hand, both HEIs and the labour market players agree that the programmes have a substantial theoretical component, which means that HEIs remain very academic and very theoretical, while companies are very practical. Also Hardin-Ramanan et al(2020) found this constraint. This is in line with the findings of Matsouka and Mihail (2016), who found that most employers consider Higher education curricula for employability that graduates arrive in the job market poorly prepared and that there is a big gap between the knowledge that graduates have and their ability to apply them in real work contexts.…”
Section: Npesmentioning
confidence: 80%
“…Based on our analysed interview findings, the challenges for higher education institutions include not only preparing a revised curriculum document annually in delivering "workready" or "industry-ready" graduates but also equipping them with the skills on how human and social capital can be strategically deployed (network with professionals) as well as strategies to assist them to become resilient to labour market challenges (Barkas et al, 2020;Hardin-Ramanan et al, 2020;Jamaludin et al, 2021;Tomlinson, 2017). In doing so, current university programs, however, do not need to oversell job prospects (Barkas et al, 2020) or forsake discipline expertise (Collet et al, 2015) because basic conceptual and technical knowledge remains the most important criterion for employers in these fields.…”
Section: Discussionmentioning
confidence: 99%
“…Human capital refers to the information and skills that graduates gain as a foundation for their future employment prospects (Tomlinson, 2017). In specific, this type of capital is concerned with what and how graduates may build links between their formal education and future employment outcomes in order to mobilise graduates' human capital and bring them closer to work opportunities (Clarke, 2018;Donald et al, 2017;Hardin-Ramanan et al, 2020;Tomlinson, 2017). Thus, situating this study within the perspective of human capital theory to employability skills within the Fourth Industrial Revolution will give graduates numerous chances to develop their human capital and encourage them to pursue a professional path.…”
Section: Employability Skills In the Twenty-first Centurymentioning
confidence: 99%
See 1 more Smart Citation